2019
DOI: 10.1039/c8fo02003e
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of arsenic bioaccessibility in raw and cooked radish using simulated in vitro digestion

Abstract: Boiled cooking should be recommended when we consume As-contaminated vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The total As content in radish roots, shoots and leaves was quantified by inductively coupled plasma mass spectrometry (ICP-MS; Agilent 7700x, USA). The sample pretreatment and detailed steps were performed according to the previously published method (Hu et al, 2019). In brief, the pre-ground raw radish samples were mineralized with nitric acid to analyze total As content.…”
Section: Determination Of As In Radishmentioning
confidence: 99%
“…The total As content in radish roots, shoots and leaves was quantified by inductively coupled plasma mass spectrometry (ICP-MS; Agilent 7700x, USA). The sample pretreatment and detailed steps were performed according to the previously published method (Hu et al, 2019). In brief, the pre-ground raw radish samples were mineralized with nitric acid to analyze total As content.…”
Section: Determination Of As In Radishmentioning
confidence: 99%
“…However, in a similar study, Toni et al showed [ 18 ] that griddling and boiling improved the bioaccessibility of As in edible mushrooms, which may be related to the selected kinds of edible fungi. Hu et al [ 31 ] studied the bioaccessibility of As in carrots, which ranged from 41.3% to 71.7% after steaming, boiling, and stir-frying, which was smaller than the bioaccessibility of As in carrots before cooking (77.2%). It validated that the bioaccessibilities of As in different food matrices were affected differently by diverse cooking methods.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary polyphenols in black rice have the function of preventing chronic diseases, but they must be digested by the human gastrointestinal tract before they can function. 148 Due to the impact of gastrointestinal digestion on the properties of bioactive compounds, it is important to analyze the changes and release of phenolic compounds during digestion. 149 The digestion test is divided into two methods: in vivo animal models and in vitro gastrointestinal digestion simulations.…”
Section: Digestive Characteristics Of Polyphenols In Processed Black ...mentioning
confidence: 99%